Localized Scleroderma Associated with Chronic Hepatitis C. (21st November 2012) - de Oliveira, Felipe Ladeira; de Barros Silveira, Luisa Kelmer Côrtes; Rambaldi, Maria Lourdes Candela; Barbosa, Fabio Cuiabano
Abstract : Hepatitis C virus has been associated with various skin conditions, such as porphyria cutanea tarda and lichen planus, as an example. The objective of this paper is based on the description of a case of localized morphea, which came years after the discovery of hepatitis C, as well as a discussion of possible relations between both diseases.